Perancangan Ulang Interior House Of Sangkuriang Dengan Pendekatan Lokalitas Kota Bandung - Wulandari Hidayat, Cahya; Sarihati, Titihan; Bayu Perdana, Aditya (Telkom University, 2024)
Hotels are buildings that provide accommodation, food, drinks, and other services for the general public. Boutique hotels are a type of luxury hotel with a limited number of rooms and unique designs that reflect local culture and history. House Sangkuriang is a 3-star boutique hotel in Bandung that promotes an Art Deco concept with a lush atmosphere. However, the application of Art Deco in its interior is not yet fully evident, and some facilities do not meet the 3-star standard. This design aims to strengthen the application of Art Deco in the interior, align facilities with 3-star standards, and create a unique and comfortable experience for visitors with a lush Art Deco ambiance. Keywords: boutique hotel, Bandung, House Sangkuriang, art deco